PSYCHOMOTOR RECOVERY AFTER INTRAVENOUS DEXMEDETOMIDINE INFUSION AS A PART OF BALANCED ANAESTHESIA – AN OBSERVATIONAL STUDY - KHALAM, ANZALNA A; VARGHESE, REGIMOL V; R, RATHEESHKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to determine the recovery of psychomotor function from balanced anesthesia with and without intravenous (IV) dexmedetomidine infusion as an adjunct. Methods: A prospective and observational study was conducted in a tertiary care teaching hospital for 12 months. A total of 170 patients (American Society of Anaesthesiologists 1 and 2) in the age group of 18–50 years scheduled for elective surgery under general anesthesia with an anticipated duration of <3 h received either dexmedetomidine infusion (Group D) or not (Group S). Recovery of psychomotor function postoperatively was assessed with trieger dot test (TDT), digit symbol substitution test (DSST), and intraoperative fentanyl requirement in both groups. Data collected were analyzed using SPSS version 16. Results: Both groups were comparable with respect to demographic variables. Psychomotor recovery assessed by TDT showed statistically significant early recovery in Group D compared with Group S. This was seen in the number of dots missed, maximum distance of dots missed as well as in the average distance of dots missed at post-operative time intervals of 30 min, 60 min, 90 min, and 120 min. Similarly, DSST revealed early recovery at these time points. There was a significant decrease in the intraoperative fentanyl requirement in Group D compared with Group S. Conclusion: The addition of dexmedetomidine to the balanced anesthetic technique significantly hastened the psychomotor recovery.